Family-Based Moral Character Development through Parental Uswatun Hasanah among Elementary School Children - Ninil Elfira; Azmatul Khairiah Sari; Armila Armila (STIT Ahlussunnah Bukittinggi, 2026)
Moral character development among elementary school students has become an important concern in contemporary education, particularly in the context of increasing challenges to children's moral and social behavior. Although character education has been widely discussed, limited studies have examined the role of parental uswatun hasanah (exemplary role modeling) as a family-based approach to strengthening children's moral character. This study aims to explore the implementation of family-based moral character strengthening through parental uswatun hasanah, identify supporting and inhibiting factors, and examine its impact on students' moral character development. A qualitative case study design was employed at a public elementary school in Indonesia. Data were collected through observations, in-depth interviews, and document analysis involving 28 participants, including parents, teachers, the school principal, and students in grades IV–VI selected through purposive sampling. The data were analyzed thematically using the Miles, Huberman, and Saldaña framework. The findings reveal that the consistent practice of parental uswatun hasanah contributes significantly to the development of children's moral character, particularly in honesty, responsibility, discipline, and respect for others. Three major themes emerged from the analysis; i) parental role modeling in religious practices, ii) moral communication and value transmission within the family, and iii) consistency in Islamic value-based parenting. The study proposes a family-based moral character framework that highlights the central role of parental exemplarity in fostering positive moral behavior among elementary school students. These findings contribute to the literature on character education by emphasizing the integration of family engagement, moral communication, and Islamic values in children's character formation.